2013
DOI: 10.1159/000350114
|View full text |Cite
|
Sign up to set email alerts
|

(-)-Epigallocatechin-3-Gallate Inhibits CC Chemokine Ligand 11 Production in Human Gingival Fibroblasts

Abstract: Background: CC chemokine ligand 11 (CCL11) is related to Th2 cells migration via CC chemokine receptor 3 (CCR3). Th2 cells are involved in the etiology of periodontal disease. However, how the infiltration of Th2 cells is controlled in periodontally diseased tissues is unknown. (-)-Epigallocatechin gallate (EGCG), the major catechin in green tea, has multiple beneficial effects, but the effects of EGCG on CCL11 production are uncertain. In this study, we investigated whether cytokines could induce CCL11 produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 26 publications
2
13
0
Order By: Relevance
“…Hirst and the colleagues reported that IL-4 synergistically enhanced CCL11 release from human airway smooth muscle cells stimulated with IL-1β [21]. We previously reported that IL-4 synergistically enhanced CCL11 production in IL-1β-stimulated human gingival fibroblasts [6]. Judging from our data and previous reports, the number of Th2 cells in inflammatory lesions might dramatically enhanced when both IL-4 and IL-1β existed because CCL11 productions positively increased.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Hirst and the colleagues reported that IL-4 synergistically enhanced CCL11 release from human airway smooth muscle cells stimulated with IL-1β [21]. We previously reported that IL-4 synergistically enhanced CCL11 production in IL-1β-stimulated human gingival fibroblasts [6]. Judging from our data and previous reports, the number of Th2 cells in inflammatory lesions might dramatically enhanced when both IL-4 and IL-1β existed because CCL11 productions positively increased.…”
Section: Discussionsupporting
confidence: 74%
“…IL-4, which is a Th2 type cytokine, is an important factor that could modulate immune response in periodontal lesion [3,4]. We previously reported that IL-4 could enhance VCAM-1 [4], CCL17 [5] and CCL11 [6] production in human gingival fibroblasts. It is known that VCAM-1 [7], CCL17 [8] and CCL11 [9] are related to Th2 cells retention and migration in inflammatory lesion.…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that TNF-α-stimulated periodontium constitution cells could produce chemokines which have already participated in neutrophils [6], Th1 cells [7], Th2 cells [8], and Th17 cells infiltration [9]. However, we do not understand the mechanism how chemokine production is controlled in periodontal lesion enough because new inflammatory mediator expressions are reported.…”
Section: Introductionmentioning
confidence: 99%
“…Further, elevated levels of activated p38α MAPK in inflamed tissue of patients with rheumatoid arthritis (RA) [3], Crohn's disease (CD) [4] and chronic obstructive pulmonary disease (COPD) [5] confirmed these key signalling molecules as therapeutic targets. Moreover, various disorders were connected with p38 MAPK signalling pathway such as artheriosclerosis [6,7] (via increased production of proinflammatory cytokines induced by oxidized low-density lipoprotein in human mast cell line and by inhibition of the formation of human macrophage-derived foam cells), platelet activation and thrombus formation [8] (through abrogation of p38 MAPKdependent phosphorylation of platelet cytosolic phospholipase A2), diabetic peripheral neuropathy [9] (by activated CD8(+)-T-cells mediating cytotoxicity toward Schwann cells), periodontal disease [10] (via modulation of CC chemokine ligand 11 (CCL11) related Th2 cells migration in human gingival fibroblasts), inflammation in human pulmonary epithelial cells [11] (through TNF-α triggered chemokine CXCL1 release) and induced proinflammatory cytokines production in macrophages [12] (via IL-17A). However, up to now, several generations of p38 MAP kinase inhibitors failed in clinical trials predominantly due to lack of efficacy and/or a poor safety profile [13][14][15].…”
Section: Introductionmentioning
confidence: 99%